Adjudication of the Alleged Role of Vitamin D in the Antimicrobial Pathway. (10th July 2012) - Higa, Gerald M.; Hicks, Jason; Isabella, Christopher
Abstract : Dynamic interactions between microorganism and host have evolved in such a way that while microbial pathogens are the cause of many human infections, a symbiotic relationship is also known to exist. Another important anomaly is that exposure to pathogenic organisms does not necessarily result in development of clinical disease. The latter conclusion infers that susceptibility to infectious disease can be modified by host-related factors. Arguably the two most prominent factors are genetic variability and immunologic status of the exposed individual. Because of the Human Genome and the HapMap projects, developments in genotyping technology have brought the possibility of identifying associations between specific genetic alterations and common diseases closer to reality. In addition, a growing body of evidence suggests vitamin D has an important contributory role in the antimicrobial pathway.